Peculiarities Of Translating Medical Terms (Texas Journal of Medical Science, 2021)
The article presents analysis results of translation of medication package inserts from English and German to Russian and Uzbek languages. Data about the frequency of use of the translation techniques that correspond to lexical and grammatical transformations in translated units of any text genre is given. The most frequently used translation techniques are identified: selection of equivalent lexical forms, combination of different techniques, calque translation, and explicatory translation